Chained-Function Waveguide Filter for 5G and beyond - Lim, Y.P. (Institute of Electrical and Electronics Engineers Inc., 2019)
In this paper, we implement a new class of filter function, namely the chained-function, in waveguide technology. A sixth-order chained-function polynomial with the seed function of order (1, 2, 3) is implemented in a WR-12 waveguide filter to provide the required out of band rejection level that satisfies a given set of filter specifications. The filter operates at 70 GHz with a theoretical in-band return loss level of 21.14 dB and a fractional bandwidth of 1.43. The design and synthesize of the chained-function waveguide filter are carried out based on a coupling matrix synthesis approach. A working simulation model using ANSYS High Frequency Structure Simulator (HFSS) is constructed to validate the filter design. The novel chained function polynomial has the ability to reduce the sensitivity with respect to manufacturing tolerance while maintaining a maximum permitted in-band insertion loss ripple. In short, the research findings lead to a high performance, low-cost and sustainable filter implementation with a minimum tuning effort pertaining to the future 5G millimeter-wave communication system. Â© 2018 IEEE.